Husbands’ knowledge and involvement in sexual and reproductive health rights of women in Bahir Dar City, Northwest Ethiopia: a community-based study - Jemberie, Mekdes Mengesha; Zewdu, Meseret; Rade, Bayew Kelkay (Frontiers in Public Health, 2024)
Background: Sexual and reproductive health rights (SRHRs) are integral elements of the rights of everyone to the highest attainable standard of physical and mental health, but it is the most underdeveloped and the least understood sphere of rights, especially in Africa including the country Ethiopia. The implementation of women's SRHRs is essential for achieving gender equality and promoting women's rights. Husbands' knowledge and involvement play a significant role in improving women practice of their SRHRs. However, there is limited information/data about the level of husbands' knowledge and involvement in Northwest Ethiopia including Bahir Dar City. Therefore, this study aimed to assess husbands' knowledge, involvement and factors influencing their involvement in women SRHRs.: Community based cross-sectional study design was conducted from March 20 to April 5, 2023, in Bahir Dar City, Northwest Ethiopia among 391 husbands. Multi-stage sampling and simple random sampling technique were applied to select kebeles and study participants, respectively. Participants were interviewed face-to-face using structured and pretested questionnaire. Binary logistic regression was applied to identify associated factors and p-value <0.05 was a cut-off point to declare statistical significance. Results: In this study, 50.6% (198/391) of the husbands had good knowledge about their wives SRHRs and 44.2% (173/391) (95% CI; 39.3-49.1%) husbands were involved when their wives practice their SRHRs. Access training/education about sexual health [AOR=5.99; 95% CI (2.7-13.2)], husbands' advance educational level [AOR=8.81; 95% CI (2.04-38), good knowledge about SRHRs [AOR=7.94; 95% CI (4.3-14.4), low monthly income (<4600 birr) [AOR=9.25; 95% CI (4.2-20.5)], and had open discussion with family members and friends about SRHRs [AOR=1.92;95% CI (1.01-3.6)] were found to have significant association with husbands' involvement.Husbands' level of knowledge on SRHRs of women and their involvement remain low. Therefore, responsible concerned bodies need to make efforts on access of trainings/education about sexual health, encourage open discussion at home despite their level of income and arrange other platforms to empower men knowledge on SRHRs would help to overcome the challenge.